MEMORI KOLEKTIF PRASASTI KEMBANG SORE SEBAGAI SUMBER BELAJAR SEJARAH LOKAL DALAM MEMPERKUAT IDENTITAS SOSIAL PEMBELAJARAN IPS - Pungky Mareta Arianti; Sinta Lidia Fitriani; Nesya Cristy Aprilina; Nia Ramadhani; Mahira Deta Naila Ansaria; Divana Jingga Aurel Lia; Agung Setiawan (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
This study aims to describe the collective memory of the Petak Village community regarding the Kembang Sore Inscription, analyze the dynamics of memory transmission across generations, and formulate its potential as a source of local history learning in Social Studies (IPS) instruction. The research employed a qualitative approach with a case study design. Data were collected through field observations, in-depth interviews with six informants consisting of the inscription caretaker, cross-generational residents (aged 50-80 years, 25-40 years, and adolescents aged 15-20 years), and document analysis. The findings reveal three main results. First, collective memory about the inscription remains strong among the older generation, begins to fade among young adults, and is limited among adolescents. Second, the community interprets the inscription's symbols (sun, moon, mountain stamp, lingga yoni, and water vessel) in the context of land ownership, fertility, and spiritual protection. Third, the inscription still functions as a village sacred site with regularly preserved rituals, making it a living heritage. The Kembang Sore Inscription has great potential as a source of social studies learning, encompassing aspects of government legality, leadership, spirituality, and social identity reinforcement. This study concludes that the community's collective memory about the inscription is still maintained but requires more effective transmission efforts to younger generations. This inscription deserves to be integrated into social studies learning through field trip methods and digital media development. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan struktur memori kolektif masyarakat Desa Petak tentang Prasasti Kembang Sore, menganalisis dinamika transmisi memori antar generasi, serta merumuskan potensinya sebagai sumber belajar sejarah lokal dalam pembelajaran Ilmu Pengetahuan Sosial (IPS). Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus. Pengumpulan data dilakukan melalui observasi lapangan, wawancara mendalam dengan enam informan yang terdiri dari juru kunci, warga lintas generasi (usia 50-80 tahun, 25-40 tahun, dan remaja 15-20 tahun), serta studi dokumentasi. Hasil penelitian menunjukkan tiga temuan utama. Pertama, memori kolektif tentang prasasti masih kuat pada generasi tua, mulai menipis pada generasi dewasa muda, dan terbatas pada generasi remaja. Kedua, masyarakat memaknai simbol-simbol prasasti (matahari, bulan, stempel gunung, lingga yoni, dan kendi) dalam konteks kepemilikan tanah, kesuburan, dan perlindungan spiritual. Ketiga, prasasti hingga kini berfungsi sebagai punden desa dengan ritual rutin yang masih dilestarikan, menjadikannya sebagai living heritage. Prasasti Kembang Sore memiliki potensi besar sebagai sumber belajar IPS, mencakup aspek legalitas pemerintahan, kepemimpinan, spiritualitas, dan penguatan identitas sosial. Penelitian ini menyimpulkan bahwa memori kolektif masyarakat tentang prasasti masih terjaga namun memerlukan upaya transmisi yang lebih efektif kepada generasi muda. Prasasti ini layak diintegrasikan ke dalam pembelajaran IPS melalui metode field trip dan pengembangan media digital.